Modification of zeolite with metallic ions improves the immobilization of phytase. (September 2021) - Lopes, M.M.; Coutinho, T.C.; Farinas, C.S.
Abstract: Phytase is an enzyme applied in several fields, but its wider use is still limited due to its high cost and poor stability, which can be overcome using immobilization techniques. Zeolites are promising support materials for enzyme immobilization, due to their attractive properties, including the capacity for modification using a simple ion exchange procedure, enabling better chemical interaction with proteins. In this work, investigation was made of the immobilization of phytase onto zeolites modified with metallic ions (Ag, Cd, Zn, Cu, Ca, Mg, and Ni). The zeolite modified with nickel reached immobilization yield of 66%, while the recovered activity (150%) indicated activation of the catalytic activity due to the presence of the metallic ion. The immobilized phytase showed excellent performance under conditions of acidic pH, reaching a relative activity up to 7 times higher than observed for its free form. Furthermore, it was possible to recover and reuse effectively the zeolite-Ni/Phytase derivative in at least 4 consecutive cycles of phytate hydrolysis reaction. The phytase immobilized onto zeolite modified with nickel presented improved properties, expanding the range of potential applications of this important enzyme. These findings demonstrate an efficient and simple protocol for enzyme immobilization onto zeolites modified with metallic ions. Graphical abstract: Image 1 Highlights: Zeolite-metallic ion system is a promising for phytase immobilization. The derivative zeolite-Ni-phytase showed a catalytic activation related to the Ni. Zeolite-Ni-phytase showed better activity than the free enzyme at acidic pH. Zeolite-Ni-phytase could be reused in at least 4 cycles of phytate hydrolysis.